2012
DOI: 10.5194/se-3-63-2012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glacial-interglacial sea-level changes on the displacement and stress field in the forearc and along the plate interface of subduction zones

Abstract: Abstract. Combined seismological, space-geodetic and numerical studies have shown that the seismicity at subduction zones may be modulated by tides and glacier fluctuations on timescales of 1-100 a, because these changes in loads on Earth's surface are able to alter the stress field in the upper plate and along the plate interface. Here we use a two-dimensional finite-element model of a subduction zone to investigate how glacial-interglacial sea-level changes affect the forearc region and the plate interface. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Thus, cyclic sea-water loading on accretionary wedges may influence tectonic activity, as evidenced by the recognition of climate-induced tectonic deformation and fault displacements (e.g. Li & Hampel 2012). Also, volcanic activity may be forced by climate changes such as deglaciation forcing volcanism in the Quaternary (e.g.…”
Section: Non-climate Related Cycles?mentioning
confidence: 99%
“…Thus, cyclic sea-water loading on accretionary wedges may influence tectonic activity, as evidenced by the recognition of climate-induced tectonic deformation and fault displacements (e.g. Li & Hampel 2012). Also, volcanic activity may be forced by climate changes such as deglaciation forcing volcanism in the Quaternary (e.g.…”
Section: Non-climate Related Cycles?mentioning
confidence: 99%
“…Previous studies have found that faults in the upper part of a subduction zone are susceptible to changes in ice and water loads (e.g., Chochran et al 2004;Luttrell and Sandwell, 2010). Li and Hampel (2012) use 2-D finite element models to show that glacial-interglacial sea level variations can be responsible for significant stress variations within convergent plates and, in turn, for the earthquake cycle of subduction thrust faults. Earthquakes are promoted during sea-level fall and delayed during sea-level rise.…”
Section: The Subduction Zones Special Issuementioning
confidence: 99%